Facing the mountain [large type] : a true story of Japanese American heroes in World War II - Brown, Daniel James, 1951- (Random House Large Print, 2021)
Draws on extensive interviews with the families of four soldiers to chronicle the special Japanese-American Army unit that overcame brutal odds in Europe while their parents were forced to surrender their homes and submit to life in concentration camps on American soil.